2018
DOI: 10.3233/jbr-180356
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory effects of extracts from Maqui berry Aristotelia chilensis in human colon cancer cells

Abstract: BACKGROUND: Anthocyanins, flavonoids and organic acids widely occurring in extracts of the fruits of Aristotelia chilensis ("Maqui"), concertedly acts on the expression of cyclooxygenase-2 (COX-2), NF-B, HT-29 and Caco-2 colon cancer cell growth inhibition and on the production of inflammatory mediators. OBJECTIVE: To assess the anti-inflammatory effects of extracts from fruits of "Maqui Berry", on the HT-29 and Caco-2 human colorectal cancer cell lines by measuring COX-2 and NF-B as well as their antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 91 publications
3
19
0
Order By: Relevance
“…The DM‐F2 fraction was selected for further experiments since the American National Cancer Institute considers an extract suitable for further analysis if its LC 50 value is lower than 30 µg/mL (Momtazi‐Borojeni, Behbahani, & Sadeghi‐Aliabadi, 2013). The obtained value (27.6 ± 1.8%) is similar to LC 50 values reported for HT‐29 and Caco‐2 human colon cancer cells (28.50 to 31.64%) when exposed to methanol:water and acetone extracts obtained from Aristotelia chilensis (Céspedes‐Acuña et al., 2018). Moreover, LC 50 were lower than those reported for HT‐29 human colon cancer cells after treatment with phenolic‐rich extracts of several berries such as black raspberry, cranberry, and strawberries, among others (Seeram et al., 2006).…”
Section: Resultssupporting
confidence: 83%
“…The DM‐F2 fraction was selected for further experiments since the American National Cancer Institute considers an extract suitable for further analysis if its LC 50 value is lower than 30 µg/mL (Momtazi‐Borojeni, Behbahani, & Sadeghi‐Aliabadi, 2013). The obtained value (27.6 ± 1.8%) is similar to LC 50 values reported for HT‐29 and Caco‐2 human colon cancer cells (28.50 to 31.64%) when exposed to methanol:water and acetone extracts obtained from Aristotelia chilensis (Céspedes‐Acuña et al., 2018). Moreover, LC 50 were lower than those reported for HT‐29 human colon cancer cells after treatment with phenolic‐rich extracts of several berries such as black raspberry, cranberry, and strawberries, among others (Seeram et al., 2006).…”
Section: Resultssupporting
confidence: 83%
“…This study provided evidence that MB extracts potently protect against CRC. Moreover, the extracts showed antioxidant and anti-inflammatory abilities in human CRC cells, as the structural feature of extracts might be associated with the inhibition of NF-κB and COX-2 [67].…”
Section: Maqui Berry (Mb) Extractsmentioning
confidence: 99%
“… 44 Additionally, it has been shown that delphinidin, cyanidin-3-glucoside, and an anthocyanin enriched maqui extract, reduces the expression of Cox2 in HaCaT cells (human keratinocyte), Raw 264.7 (murine macrophage) and Caco-2 cells (human colorectal adenocarcinoma), which has antiapoptotic effects in endometrial cancer. 14 , 18 , 19 , 45 Additionally, other polyphenols present in maqui fruit, such as quercetin, kaempferol, and myricetin, have also been shown to induce apoptosis in some cancer cell lines. 46 - 48 …”
Section: Discussionmentioning
confidence: 99%